Effect of Plasticizer Concentration on the Properties of Hydroxypropyl Cellulose (HPC) Film Enhanced with Sodium Dehydroacetate - Passakorn KINGWASCHARAPONG; Fumina TANAKA; Arisa KOGA; Supatra KARNJANAPRATU; Fumihiko TANAKA (My University, 2023)
In the development of edible films based on hydroxypropyl cellulose (HPC) with sodium dehydroacetate (SD) as an antifungal agent, the effect of various concentrations (20, 30, and 40% based on HPC) of plasticizers (glycerol and sucrose) on the film properties was investigated.The HPC-based film with glycerol showed transparency, while the film with sucrose showed turbid and opaque (P < 0.05).The HPC film without plasticizers used as a control had high rigidity and was brittle.This property was improved when glycerol was added to the film (P < 0.05).The HPC-glycerol film had low water vapor barrier properties due to its high moisture content, especially when used at high concentrations.The incorporation of sucrose in HPC film had no marked impact on moisture content, water vapor permeability, and mechanical properties compared to control.The rough and heterogeneous morphology of the films was dominant in the film contained sucrose.FTIR spectra showed that the peaks of the glycerol mixed films were shifted to lower wavelengths compared to the control and sucrose mixed films.This is due to the increase of -OH group in the film matrix of HPC film.These results suggest that glycerol is a more promising plasticizer than sucrose to plasticize in the matrix of HPC films.In particular, HPC films containing 20% (w/w of HPC content) glycerol possessed satisfactory film properties and could be formulated as edible films and coatings.
Keywords: Plasticizer; Hydroxypropyl cellulose; Methyl cellulose; Polymer Science and PVC